The “Public” in Public Schools: A School Board Debate - Gaskell, Jane (Canadian Journal of Education/Revue canadienne de l’éducation, 2001)
In this article I explore the debate about common schooling in an increasingly diverse and less deferential Canada. In a case study, I describe how one school board reacted when dissatisfied parents tried to establish a traditional school. The board rejected two such proposals, consistent with its policy of inclusion. The parents made it clear that there was no agreement about the meaning of inclusion and the nature of schooling in the district. This “politics of difference” poses questions about teachers’ work, democratic decision-making, and school policy that are not addressed when school choice is treated as a market phenomenon. Utilisant une étude de cas, l’auteure fait état des discussions entre une commission scolaire et certains parents au sujet de la politique d’inclusion en vigueur dans le Conseil scolaire. Les parents ont mis en relief l’absence de consensus quant au sens du terme « inclusion » et au type d’éducation à mettre en œuvre dans la circonscription. La politique traditionnelle de la différence suscite des questions qui ne sont pas considérées quand le choix de l’école est traité comme un simple phénomène de marché.